Regional Variations in Awareness and Adoption of Dairy Management Interventions among Farmers of Pathankot and Kathua Districts - Singh, Ravdeep; Kumar Sharma, Rakesh; Singh, Jaswinder; Kasrija, Rajesh; Deshmukh, Bharti; Hon parkhe, Mrigank (The Indian Journal of Animal Reproduction, 2026)
This study aimed to find the awareness and adoption of scientific dairy management interventions among farmers in Pathankot (Punjab) and Kathua (Jammu & Kashmir. A multistage random sampling technique was employed to select 80 respondents (40 per district), covering five management domains: calf care, feeding, housing, reproduction and health care. Responses were recorded on a binary scale (Yes = 1, No = 0) and data were analysed using Student’s t-test, with p < 0.05 considered significant. The results revealed marked regional disparities. The overall mean adoption score was sig nificantly higher in Pathankot (0.67 ± 0.06a) compared to Kathua (0.56 ± 0.06b), indicating greater scientific orientation among Punjab farmers. Significant differences (p < 0.05) were found in key indicators such as feeding of concentrates and mineral mixtures (0.62 ± 0.07a vs 0.40 ± 0.07b), silage preparation (0.55 ± 0.07a vs 0.27 ± 0.07b), awareness of age at first insemination (0.95 ± 0.03a vs 0.77 ± 0.06b), AI preference (0.87 ± 0.05a vs 0.70 ± 0.07b), semen quality (0.77 ± 0.06a vs 0.62 ± 0.07b), and reproductive record keeping (0.47 ± 0.07a vs 0.25 ± 0.06b). Pathankot also showed higher adoption of prophylactic disease measures (0.32 ± 0.07a vs 0.15 ± 0.05b), reflecting its stronger veterinary network and exten sion exposure. The study underscores the need for targeted capacity-building, farmer-centric training and policy-driven infrastructure support in emerging dairy regions. Strengthening integrated dairy management will ensure sustainable productivity and equitable dairy development across northern India.
Keywords: Dairy farming; Breeding management; Feeding practices; Health care; Awareness; Pathankot; Kathua